Pengaruh Harga dan Promosi terhadap Keputusan Pembelian Air Minum dalam Kemasan (AMDK) Merek Aguen - Dicky Bimas Prayoga; Darham Wahid; Yudhi Novriansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of price and promotion on purchasing decisions for Aguen brand Bottled Drinking Water (AMDK). The method used is quantitative descriptive research with SPSS 26 analysis of 96 respondents. The results of the study indicate that the price variable (X1) has a significant effect on purchasing decisions (Y), with a calculated t value of 9.360 and significance (0.00<0.05). Likewise, the promotion variable (X2) has a significant effect on purchasing decisions (Y) with a calculated t value of 6.085 and significance (0.00<0.05). Simultaneously, price (X1) and promotion (X2) also have a significant effect on purchasing decisions (Y), with a calculated F value of 107.470 and significance (0.00<0.05). The coefficient of determination (R²) value of 0.698 indicates that 69.8% of the variation in purchasing decisions can be explained by price and promotion factors, while the remaining 30.2% is influenced by other factors not examined in this study.